Smart OBE Academic Planner (SOBEAP): A Novel Approach for Integrating Self-Efficacy Among Student in Higher Education - Aziman, Abdullah; Wan Nor Afiqah, Wan Othman; Adzhar, Kamaludin; Awanis, Romli; Mohd Faaizie, Darmawan (Centre for Teaching and Learning, IIUM and Darul Syakir Enterprise, 2018)
In Malaysia, Outcomes Based Education (OBE) is translated through the implementation of Malaysia Qualification Framework (MQF) which is a legal requirement (Malaysian Qualifications Agency Act 2007) for higher education institution in securing program accreditation. However, there are challenges in OBE implementation which it is still at nurturing stage among educators while among student, it might be still at infancy stage and took some time to be established and culturized. With Industry Revolution 4.0 (IR4), universities are demanded to adopt new way of how academic matters been managed, operated and rapidly improvised with targeted opportunities and calculated risks. One of the potential technologies in IR4 to deal with such issues is by using digital technology like software based visual analytics approach. This technology can assist student to manage their academic performance through data driven decision-making approach which strongly impact student’s self-efficacy level. Our study aims to develop a technology called Smart OBE Academic Planner (SOBEAP) to instill self-efficacy while internalizing OBE among student. This technology adopts visual digital analytics approach with decision modeling based on MQF. Key outcomes from this study produced specific decision models for student to manage their academic performance by adopting self-efficacy skills through SOBEAP. It capable to analyze the effectiveness of student’s study strategies while producing insights (opportunity and risk) for student to manage their future academic performance.